Sociological Assessment Of The Entrepreneurial Activity Of The Population In The Service Sector - Maftuna Khudayarova (Academia Open, 2025)
Background: The service sector serves as a critical driver for enhancing entrepreneurial activity and addressing socio-economic challenges such as unemployment and poverty in developing economies. Knowledge Gap: While Uzbekistan has established comprehensive legal and institutional frameworks to support entrepreneurship, limited empirical research exists on the actual entrepreneurial activity levels and barriers faced by populations at the community (mahalla) level in the service sector. Aims: This study conducts a sociological assessment of entrepreneurial activity in Samarkand region's service sector, evaluating socio-economic factors, existing barriers, and opportunities through quantitative and qualitative methods. Results: Survey data from 496 respondents revealed that although 74.8% expressed desire to start businesses, only 25.1% possessed adequate family assets for entrepreneurial ventures. Key obstacles identified included insufficient capital-property resources (42.2% needed machinery/equipment, 47.1% required production buildings), limited financial literacy, and weak institutional support at the neighborhood level, with 80.7% reporting no practical assistance from local government programs. Novelty: This research employs a mahalla-based methodological approach to assess entrepreneurial readiness, providing granular insights into community-level barriers previously overlooked in regional development studies. Implications: Findings underscore the necessity for targeted interventions including enhanced financial literacy programs, improved neighborhood-level institutional support mechanisms, and comprehensive capital-property assistance schemes to effectively stimulate entrepreneurial activity among Uzbekistan's population.Highlight : The study reveals that 74.8% of respondents desire to start businesses, but only 25.1% have adequate opportunities to utilize family assets as initial capital. Major barriers include lack of machinery and equipment (42.2%), production facilities (47.1%), and reliance on mixed financing sources combining bank loans and personal funds (39.6%). Institutional support remains inadequate, with 80.7% of respondents receiving no practical assistance from neighborhood-level government programs, indicating gaps in community-based entrepreneurship development mechanisms. Keywords : Service Sector, Entrepreneurial Activity, Sociological Analysis, Economic Activity, Social Factors